Conference Report: New setting for the Land O'Lakes bioanalytical conference. (November 2013) - DeMuth, James E; Ho, Stacy; Briscoe, Chad; Cyronak, Matthew; Fluhler, Eric N; Ji, Qin C; Sriraman, Priya
The University of Wisconsin bioanalytical conference is presented each year by the Extension Services in Pharmacy, the professional development department within the School of Pharmacy. The purpose of this 3-day conference was to provide an educational forum to discuss issues and applications associated with the analysis of xenobiotics, metabolites, biologics and biomarkers in biological matrices. The conference was designed to include and encourage an open exchange of scientific and methodological applications for bioanalysis. To increase the interactive nature of the conference the program was composed of a mixture of lectures, interactive discussions, poster sessions and roundtables. This paper summarizes the presentations at the Fourteenth Annual Conference, offered in a new venue.